2010
DOI: 10.1007/s00018-010-0581-6
|View full text |Cite|
|
Sign up to set email alerts
|

HLA-G in organ transplantation: towards clinical applications

Abstract: HLA-G plays a particular role during pregnancy in which its expression at the feto-maternal barrier participates into the tolerance of the allogenic foetus. HLA-G has also been demonstrated to be expressed in some transplanted patients, suggesting that it regulates the allogenic response. In vitro data indicate that HLA-G modulates NK cells, T cells, and DC maturation through its interactions with various inhibitory receptors. In this paper, we will review the data reporting the HLA-G involvement of HLA-G in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 101 publications
0
36
0
1
Order By: Relevance
“…It was found that the HLA-G 14 bp insertion polymorphism in the 3´UTR is responsible for a decrease in the mRNA level of most membrane and soluble isoforms [15]. The possible impact of the HLA-G 14 bp variant on kidney graft be up-regulated by stressors such as hypoxia, cytokines like IFN-g, TNF, IL-10, TGF-b, immunosuppressive agents or progressive doses of progesterone [34,35]. In relation to HLA-G expression, the time-course of serum HLA-G in patients after kidney transplantation has been examined by only few studies to date [18,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the HLA-G 14 bp insertion polymorphism in the 3´UTR is responsible for a decrease in the mRNA level of most membrane and soluble isoforms [15]. The possible impact of the HLA-G 14 bp variant on kidney graft be up-regulated by stressors such as hypoxia, cytokines like IFN-g, TNF, IL-10, TGF-b, immunosuppressive agents or progressive doses of progesterone [34,35]. In relation to HLA-G expression, the time-course of serum HLA-G in patients after kidney transplantation has been examined by only few studies to date [18,31].…”
Section: Discussionmentioning
confidence: 99%
“…The explanation of such HLA-G expression is mostly unknown and needs to be elucidated more precisely. It was observed that individual immunosuppressive agents can decrease HLA-G expression; however the sHLA-G levels are still higher in patients without rejection [35]. acceptance has been investigated by various authors, but the results are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In physiological conditions, HLA-G expression was also found in erythroid precursors, cornea, thymic medulla and pancreatic islets (8,(9)(10)(11). However, HLA-G can be neoexpressed in pathological conditions including cancers, transplantation, and inflammatory and autoimmune diseases and viral infections (3,5,12,13).…”
Section: Mechanisms Of Hla-g Involved In Tumor Immunologymentioning
confidence: 99%
“…Many HLA-G functions were described in vitro, because its expression is critically dependent on microenvironmental parameters. Based on all these findings, it is clear that there is a pathologic significance of HLA-G expression in vivo in the contexts of cancer (26), transplantation (27), autoimmune diseases, inflammatory diseases, and viral infections (28). …”
Section: Modulation Of Regulatory/suppressor Cellsmentioning
confidence: 99%